Pobreza e saúde mental: uma análise psicossocial a partir da perspectiva dos usuários do Centro de Atenção Psicossocial (CAPS) - Nepomuceno, Bárbara Barbosa (2013)
The present study is dedicated to analyze the relation between two complex phenomena, poverty and mental health. Considering that the majority of users of the public mental health comes from social contexts marked by low education, poor living conditions, unemployment and low income, the referring research is relevant. Poverty is a multidimensional phenomenon that is not restricted to the sphere of material privation, reaching psychosocial dimensions, resulting in the production of subjectivities and unique ways of life. Mental health, in turn, is a complex and multidetermined phenomenon, which is influenced by the biological, psychological, social, cultural, economic, and moral order being, therefore, necessary to an understanding of the health-disease process consider the sociocultural and economic context in which this takes place and their individual experiences. Given this, the general objective of the study is to analyze the implications of the psychosocial aspects of poverty in the health-mental disease users of Psychosocial Attention Center (CAPS). The specific objectives are: identify psychosocial aspects of poverty in the life of users of CAPS; analyze the health-mental disease process of poor users of CAPS; and comprehend the relation between poverty and the health-mental disease process. The research is qualitative in nature, developed with five users of Community CAPS of Bom Jardim. As instruments for the construction and analysis of data were used Multidimensional Poverty and Individual Interview Questionnaire. For data analysis was conducted the analysis of content, performed with the help of the software ATLAS.ti 5.2. As a result realizes that there is a circularity relationship between poverty and psychic suffering. There are frequent in the experience of poverty feelings of oppression, guilt, shame, humiliation and uncertainty of the future, continued stress, ethical-political suffering, among other implications producers of psychic suffering. On the other hand, no access to health care can effectively contribute to disease chronification and a consequent limitation in the ability to earn income from subject. Spirituality and social support net are potent to fight poverty and bring positive impacts on protection and recovery of health of the subject.